2019
DOI: 10.1049/iet-pel.2019.0302
|View full text |Cite
|
Sign up to set email alerts
|

Model, design and implementation of a low‐cost HIL for power converter and microgrid emulation using DSP

Abstract: In this study, the authors propose a method to implement a low-cost hardware-in-the-loop (HIL) system for power converters and microgrids design, test and analysis. This approach uses a digital signal processor (DSP) Texas Instruments as the HIL core. All the differential equations of the power converters are solved in real-time by the DSP and displayed in the digital-to-analogue outputs. Three different converters are modelled in this study: boost converter, single-phase inverter connected to the grid and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, it is nearly impossible to use microprocessors for high-frequency power converters in RT because of the small needed simulation step. For instance, a digital signal processor (DSP)-based HIL system for power converters such as Boost converter with a time step of 1 µs was proposed in [14]. Using the rule of 100 simulation steps per switching period, that would limit the switching period to a minimum of 100 µs and therefore switching frequencies under 10 kHz.…”
Section: Hil Modelmentioning
confidence: 99%
“…However, it is nearly impossible to use microprocessors for high-frequency power converters in RT because of the small needed simulation step. For instance, a digital signal processor (DSP)-based HIL system for power converters such as Boost converter with a time step of 1 µs was proposed in [14]. Using the rule of 100 simulation steps per switching period, that would limit the switching period to a minimum of 100 µs and therefore switching frequencies under 10 kHz.…”
Section: Hil Modelmentioning
confidence: 99%
“…The same platform is used to test HIL of a boost converter and a full-bridge in power electronics applications [19]. Furthermore, a HIL implementation using a DSP LaunchPad C2000 Delfino F28377S is presented for microgrids applications in [20]. Three different converters are modelled in this study to validate the capabilities of the proposed DSP based HIL platform.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is challenging to carry out a precise comparison of them, because most of the low-cost platforms are not commercially available and they are case a case implemented by research groups, tailored to a particular application. However, using the comparison reported in [20], it is concluded that the control systems implemented utilising some DSP platforms, can achieve time steps as low as 860 ns, higher than that achievable with the (relatively high cost) Typhoon system (≈560 ns) but still good enough to represent IGBTs in some typical application, for instance, microgrids, where the power converter switching frequency is about 10 kHz. As discussed in [8], the implementations based on FPGAs are also relatively low-cost alternatives for HIL and RTCP, achieving applications with low time steps.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent paper [1], the authors have shown that it is possible to achieve Ts1thinmathspaceμs for RT simulation of a power converter using the new generation of DSP processor. Slower than the FPGA approach, however easier to program, due to the high‐level language (C + +), with very low implementation cost, free software and friendlier environment for all engineering community.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a digital model interfaced with real controllers and actuators running in RT can reduce cost and time for testing ideas. In addition, it provides the security of not working with real variables like high voltages, high current, high speeds etc [1].…”
Section: Introductionmentioning
confidence: 99%